ANALISIS MANAJEMEN RISIKO BISNIS - Mudrika Berliana As Sajjad; Salsabila Dea Kalista; Mualif Zidan; Johan Christian (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2020)
Small, Medium Enterprises or commonly called SME are also needed to defend themselves in competition, besides SME are also required to face some global challenges, in facing global challenges this can be done by innovating products and services, and developing human resources and technology, are also needed in terms of increasing marketing areas. For this reason, risk management is needed to anticipate or reduce the likelihood of these risks by analyzing risk management. Keywords: business, risk management, sme.